STRATEGI BRANDING IMAGE DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMKS NU KOTA TASIKMALAYA - Azzahra, Dewi Amalia; Komalasari, Imas (Institut Nahdlatul Ulama Tasikmalaya, 2025)
Marketing management is crucial in maintaining the existence of educational institutions. Branding image as a marketing activity aims to introduce and display the distinctive characteristics as the identity of a product or service to the general public. By building a branding image to create a positive image, this can improve the quality of educational institutions. The aim of this research is to analyze and describe branding image strategies in improving the quality of education at SMKS NU Tasikmalaya City. The research method used is field research with a qualitative approach. Data collection techniques were carried out using observation, interviews and documentation. Data analysis techniques include data reduction, data presentation and verification. The research results show that the branding image strategy that is built is through: 1) Brand identity, by highlighting the brand of Aswaja schools, technology schools, low-cost schools. 2) Brand positioning, by upholding the values of Ahlussunnah Wal Jama'ah An-Nahdliyah, conveying the school's aim as community service through the modern education sector, and aspiring to produce graduates who excel in Aswaja and in the IT field. Forming a logo with a philosophy rich in Islamic values. It has the tagline: small, beautiful, powerful and has the song Hubbul Wathon and the IPNU IPPNU march. 3) Brand personality, by referring to the values of Ahlussunnah Wal Jama'ah An-Nahdliyah as well as positive Islamic character that is instilled in daily practice. As for improving quality through: 1) Quality Planning, with deliberations and discussion meetings with the school committee, deputy principals, and parents; designing and creating learning programs; make a financing budget plan for the program that has been formed; and carry out the main tasks and functions that have been determined in accordance with the analysis of customer needs in the program. 2) Quality Control, by carrying out monitoring and evaluation. 3) Quality Improvement, by maximally increasing the quality and capacity of human resources and infrastructure according to current developments.